BAT, CSR and Lobbying - Williams, Sarah (2008)
Due to the nature of their product, tobacco companies face much criticism from many fronts, particularly the media and NGOs. This public criticism has meant tobacco companies strive to implement sound and commendable CSR principles, initiatives, and codes, often voluntarily reporting on their CSR or sustainability activities.